STUDY OF THE DEPENDENCE OF THE AMOUNT AND COMPOSITION OF FIBROUS WASTE ON THE CONSTRUCTION OF THE WORKING PARTS OF THE CLEANING MACHINE - Mirzabayev Jamoliddin Bahriddinovich (Journals Park Publishing, 2024)
Cleaning cotton fibre in this article performance parameters of the machines were studied. Factors affecting the implementation of the approval process and emerging parameters were selected. A standard matrix recommended for a three-factor experiment was used. The test matrix was created and the experimental results were processed. Testsoptimal conditions of the amount of fibres suitable for spinning in the fibre waste according to the analysis studies have been carried out.
Keywords: cleaning, perforated surface, hole diameter on the surface, drum speed, distance between drum and surface, matrix, full factor experiment.